2004
DOI: 10.1002/cvde.200306288
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Ruthenium Thin Films from Ru(thd)3 and Oxygen

Abstract: Ruthenium thin films were grown by atomic layer deposition (ALD) from tris(2,2,6,6-tetramethyl-3,5-heptanedionato)-ruthenium [Ru(thd) 3 ] and oxygen, at temperatures between 325 C and 450 C. All the films were polycrystalline metallic ruthenium as analyzed by X-ray diffraction (XRD). Impurity contents of the films (< 2.9 at.-% H, < 1.9 at.-% C, and < 5.5 at.-% O) were nearly independent of the Ru(thd) 3 pulse time as analyzed by time of flight elastic recoil detection analysis (TOF-ERDA). The films had resisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
156
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(165 citation statements)
references
References 32 publications
8
156
1
Order By: Relevance
“…where R is the ideal gas constant, Similar behaviors were also observed in ALD Ru film depositions from Ru(thd) 3 , [6] RuCp 2 [4,5] and Ru(EtCp) 2.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…where R is the ideal gas constant, Similar behaviors were also observed in ALD Ru film depositions from Ru(thd) 3 , [6] RuCp 2 [4,5] and Ru(EtCp) 2.…”
Section: Resultssupporting
confidence: 70%
“…The Saturation of the growth rate with increasing temperature was also observed for the Ru(thd) 3 and RuCp 2 systems, which suggests these ALD processes follow a reaction mechanism similar to the one discussed by T. Aaltonen et al: Ru films are deposited by oxidizing the precursor ligands with dissociatively adsorbed oxygen from the subsurface region. [4,6] The resistivity is near 10 ·cm for deposition temperatures from 320 The film resistivity was calculated from the thickness measured by X-ray reflectivity (XRR) (Scintag XDS2000) multiplying the sheet resistance measured by a four-point probe. The morphology was studied by scanning electron microscope (Zeiss FESEM Ultra55) and atomic force microscopy (Asylum MFP-3D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 For STO, the method has already shown promise to keep a low leakage current ͑ϳ1 ϫ 10 −8 A / cm 2 ͒ and a low EOT value ͑1.5 nm͒. 10 In the past years, numerous metalorganic precursors, such as Ru͑thd͒ 3 , 11 Ru͑acac͒ 3 , 12,13 RuCp 2 , 12,14-17 and Ru͑EtCp͒ 2 , [17][18][19] have been used with O 2 gas for Ru ALD. Employing RuCp 2 , Aaltonen et al 20 showed that these processes rely on the ability of Ru to dissociatively chemisorb O 2 , providing atomic O necessary for the oxidation of the precursor ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The growth per cycle is 0.5 Å/cycle, which is higher than previously reported for ruthenium ALD. [22][23][24][25][26][27][28] There is an initiation delay of approximately 10 cycles before steady-state ALD of Ru is achieved. This delay is quite low compared to typical noble metal ALD, which often exhibits > 50-100 cycles of initiation delay.…”
mentioning
confidence: 99%